Augusto Del Noce kaip postulatyvaus ateizmo kritikas. - Markevičius, Domantas (Problems / Problemos, 2020)
In this article I seek to clarify the relation between the ideas of modernity and secularization in the thought of Augusto Del Noce, thus countering the argument that he is the 'enemy' of modernity and secularization. Contextualizing Del Noce's place within the wider reflection of the problem of secularization in the 20th century European and Italian philosophy, I argue that his position on modernity and secularization cannot be squeezed into the bipolar 'modern' vs. 'antimodern' opposition, as stated by some of his critiques. I conclude that Del Noce should be regarded not as the 'enemy' of modernity or secularization but rather as the critic of postulatory atheism that presents itself as the inevitable outcome of the modern historical process.